Comparative analysis of the antibacterial activity of some phytolectins - Nair, Sindhu Syama; Madembil, Nithyakala Chandera; Nair, Preetha; Raman, Saraswathi; Veerabadrappa, Somashekharaiah Beeranahalli (International Current Pharmaceutical Journal, 2013)
The aim of this work was to analyse the comparative effects of the antibacterial properties of partially purified lectins from the seeds of Artocarpus heterophyllus (jack fruit), Canavalia ensiformis (jack bean), Lens culinaris (lentil) and Pisum sativum (pea) against the bacteria Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa. The lectins were isolated by partial purification using ammonium sulphate precipitation and dialysis. The antimicrobial activity was studied using agar well diffusion method. The results showed that the Jack fruit lectin had a potent anti-bacterial activity against S. aureus, B. subtilis, E. coli and P. aeruginosa whereas Pea and jack bean lectin were found to be effective bacteriostatic agents which reduced the growth of bacteria and lentil lectin showed the least antibacterial activity. A comparison of the antibacterial activity of phytolectins with conventional antibiotics namely ampicillin and tetracycline was also carried out. Studies revealed that the antibacterial activities of the conventional antibiotics are higher than that of the plant extracts at the same concentration in accordance to literature. DOI: http://dx.doi.org/10.3329/icpj.v2i2.13192 International Current Pharmaceutical Journal 2013, 2(2): 18-22